Robust analysis method for acoustic properties of biological specimens measured by acoustic microscopy. (20th April 2018) - Arakawa, Mototaka; Mori, Shohei; Kanai, Hiroshi; Nagaoka, Ryo; Horie, Miki; Kobayashi, Kazuto; Saijo, Yoshifumi
Abstract: We proposed a robust analysis method for the acoustic properties of biological specimens measured by acoustic microscopy. Reflected pulse signals from the substrate and specimen were converted into frequency domains to obtain sound speed and thickness. To obtain the average acoustic properties of the specimen, parabolic approximation was performed to determine the frequency at which the amplitude of the normalized spectrum became maximum or minimum, considering the sound speed and thickness of the specimens and the operating frequency of the ultrasonic device used. The proposed method was demonstrated for a specimen of malignant melanoma of the skin by using acoustic microscopy attaching a concave transducer with a center frequency of 80 MHz. The variations in sound speed and thickness analyzed by the proposed method were markedly smaller than those analyzed by the method based on an autoregressive model. The proposed method is useful for the analysis of the acoustic properties of bilogical tissues or cells.